Tubulin Inhibitor Identification by Bioactive Conformation Alignment Pharmacophore-Guided Virtual Screening - Nagarajan, Shanthi; Choi, Min Jeong; Cho, Yong Seo; Min, Sun-Joon; Keum, Gyochang; Kim, Soo Jin; Lee, Chang Sik; Pae, Ae Nim (WILEY, 2015)
Microtubules are important cellular component that are critical for proper cellular function. Microtubules are synthesized by polymerization of alpha beta tubulin heterodimers called protofilaments. Microtubule dynamics facilitate proper cell division during mitosis. Disruption of microtubule dynamics by small-molecule agents inhibits mitosis, resulting in apoptotic cell death and preventing cell cycle progression. To identify a novel small molecule that binds the alpha beta tubulin interface to affect microtubule dynamics, we developed a bioactive conformation alignment pharmacophore (BCAP) model to screen tubulin inhibitors from a huge database. The application of BCAP model generated based on the known alpha beta-tubulin interface binders enabled us to identify several small-molecules that cause apoptosis in human promyelocytic leukemia (HL-60) cells. Virtual screening combined with an in vitro assay yielded 15 cytotoxic molecules. In particular, ethyl 2-(4-(5-methyl-3-nitro-1H-pyrazol-1-yl)butanamido)-4-phenylthiophene-3-carboxylate (H05) inhibited tubulin polymerization with an IC50 of 17.6 (mu M) concentration. The virtual screening results suggest that the application of an unbiased BCAP pharmacophore greatly eliminates unlikely compounds from a huge database and maximizes screening success. From the limited compounds tested in the tubulin polymerization inhibitor (TPI) assay, compound H05 was discovered as a tubulin inhibitor. This compound requires further structure activity optimization to identify additional potent inhibitors from the same class of molecules.
Keywords: BIOLOGICAL EVALUATION; ANTIMITOTIC AGENTS; BETA-TUBULIN; POLYMERIZATION INHIBITOR; POTENT INHIBITORS; BINDING-SITES; DERIVATIVES; COLCHICINE; DISCOVERY; INSIGHT